Rekonstruksi Epistemologi Ushul Fiqh pada Era Artificial Intelligence: Telaah Konseptual terhadap Posisi AI dalam Proses Istinbāṭ Hukum Islam - Razaq Hammam Alamsyah; Zainal Arif (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
The rapid advancement of Artificial Intelligence (AI) has fundamentally transformed the production, organization, and dissemination of knowledge, including within the field of Islamic studies. While AI significantly enhances access to Islamic sources and accelerates legal research, its increasing role in generating legal arguments raises fundamental epistemological questions concerning its position within the methodology of uṣūl al-fiqh. This study aims to reconstruct the epistemology of uṣūl al-fiqh in the era of Artificial Intelligence by examining the epistemological status of AI in the process of istinbāṭ (Islamic legal reasoning). Employing a qualitative library research approach combined with conceptual analysis, this study critically examines classical and contemporary literature on uṣūl al-fiqh, Islamic legal theory, and Artificial Intelligence. The findings demonstrate that AI does not alter the normative foundations of Islamic law but transforms the ecosystem through which Islamic legal knowledge is produced and managed. Although AI possesses remarkable capabilities in literature retrieval, comparative analysis, argument mapping, and large-scale information processing, it lacks the normative reasoning, ethical consciousness, methodological competence, and moral accountability required for ijtihād. Consequently, AI cannot function as a source of law or as a mujtahid. The study proposes a Methodological Integration Model of Uṣūl al-Fiqh and Artificial Intelligence, positioning AI as an epistemic and methodological instrument that supports legal research while preserving human scholars as the sole holders of epistemological authority in Islamic legal reasoning. This model constitutes the principal novelty of the research by shifting the discussion from the legality or ethics of AI toward its epistemological integration within uṣūl al-fiqh, thereby providing a conceptual framework for developing Islamic legal studies that remains methodologically authentic while embracing technological innovation.